Islam dan Nasionalisme: Studi Atas Pergumulan Islam dan Nasionalisme Masa Pergerakan Nasional Indonesia - Hairiyah, Hairiyah (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2022)
Abstract: The discourse of Islam and nationalism became an interesting topic of conversation at the beginning of the 20th century when the Islamic world intersected with the idea of a Western-style nation-state in the Islamic world. The nation-state concept is considered a-historical for Muslim societies. Almost all Muslim countries in the third world, including Indonesia, experience nation-state problems in finding their national identity and character (nation character buildings). Especially in Indonesia, this kind of nation-state problem has sometimes not been completely resolved which in turn will always give rise to the "Islam vs. State” with a dichotomous designation; religious state (diniyyah) and a secular state (la diniyyah). Opposition and dichotomy like this will become an obstacle in the administration of the state in the context of a nation-state. This paper uses an analytical-historical approach that is focused on the role of Sarekat Islam (SI) in the struggle for Islamic politics during the period of the national movement. This organization breathed the spirit of nationalism based on Islam for the first time in Indonesia. The current existence of political Islam should follow in the footsteps of Sarekat Islam, in upholding nationalism as a nation, Muslims must be able to become pioneers in maintaining harmony in a very pluralistic society.Keywords: Islam, Nationalism, Politic Abstrak: Wacana Islam dan Nasionalisme menjadi perbincangan menarik pada awal abad ke 20 ketika dunia Islam bersinggungan dengan ide nation-state ala Barat ke dunia Islam. Konsep nation-state dianggap a-historis bagi masyarakat Muslim. Hampir semua negara Muslim di dunia ketiga termasuk Indonesia, mengalami problem nation-state dalam mencari identitas dan karakter kebangsaannya (nation character buildings). Khususnya di Indonesia, problem nation-state semacam ini terkadang belum terselesaikan tuntas yang pada gilirannya akan selalu melahirkan penghadapan “Islam vs. Negara” dengan sebutan yang dikotomis; negara agama (diniyyah) dan negara sekuler (la diniyyah). Pertentangan dan dikotomi seperti ini akan menjadi ganjalan dalam penyelenggaraan negara dalam konteks nation-state. Tulisan ini menggunakan pendekatan analytical-historis yang difokuskan pada peran Sarekat Islam (SI) dalam pergumulan politik Islam pada masa pergerakan nasional. Organisasi inilah yang menghembuskan semangat nasionalisme yang berbasiskan Islam pertama kali di Indonesia. Eksistensi politik Islam saat ini seharusnya mengikuti jejak Sarekat Islam, dalam menegakkan nasionalisme berkebangsaan, umat Islam harus bisa menjadi pelopor dalam menjaga kerukunan hidup bermasyarakat yang sangat majemuk. Kata Kunci: Islam, Nasionalisme, Politik